Pyoderma gangrenosum‐like lesions in the setting of IgA cutaneous vasculitis: Favourable response to adalimumab - Hitomi Sugino; Hikaru Kawahara; Kayo Yamamoto; Etsuko Okada; Yu Sawada (Wiley, 2024)
Abstract Pyoderma gangrenosum is a rare inflammatory skin disease classified within the group of neutrophilic dermatoses, and clinically characterised by painful, rapidly evolving cutaneous ulcers with undermined, irregular, erythematous‐violaceous edges. Underlying diseases include rheumatoid arthritis, inflammatory bowel disease, haematopoietic malignancy, and aortitis syndrome. However, there was a limited number of cases of concomitant pyoderma gangrenosum and IgA vasculitis. Herein, we report a case presenting persistent large skin wounds as a diagnosis of pyoderma gangrenosum in the setting of IgA cutaneous vasculitis, which was successfully treated by a TNF‐α inhibitor. A 67‐year‐old obese female presented palpable purpura on her lower extremities. A skin biopsy taken from the purpuric eruption showed leukocytoclastic vasculitis with IgA and C3 depositions in the vessel walls of the upper dermis, leading to the diagnosis of IgA vasculitis. Small skin ulcers rapidly expanded in several days, eventually developing perforating skin ulcers with irregular erythematous and violaceous edges on both lower extremities following the tapered oral prednisolone at a dose of 25 mg per day. Based on the clinical manifestation and histological analysis, we diagnosed her skin wound as pyoderma gangrenosum. After the adalimumab administration, the spreading ulceration was dampened, leading to the acceleration of wound epithelialisation.